Outcomes of surgical repair versus primary tenodesis for proximal Rectus Femoris avulsion injuries in professional athletes - Kayani, B.; Singh, S.; Chang, J. S.; Magan, A. A.; Plastow, R.; Haddad, F. S. (The American Journal of Sports Medicine, 2021)
Background: Surgical repair of proximal rectus femoris avulsion injuries is associated with prolonged periods of rehabilitation and highly variable risk of injury recurrence. Surgical tenodesis of these injuries is often reserved for recurrent injuries or revision surgery. To our knowledge, the outcomes of proximal rectus femoris avulsion injuries treated with surgical repair versus primary tenodesis have not been previously reported.